2011
DOI: 10.1177/1090820x11402493
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Nonablative 1540-nm Laser Treatment of Striae Distensae in Fitzpatrick Skin Types II to IV: Clinical and Histological Results

Abstract: Positive safety and efficacy results with the fractional nonablative 1540-nm erbium:glass laser for the treatment of striae rubra and striae alba ranging in maturation age from one to 40 years was demonstrated in Fitzpatrick skin types II to IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
60
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 32 publications
2
60
1
3
Order By: Relevance
“…The histological findings in the present study are in agreement with those of Jiménez et al [15], who used PDL, and in agreement with De Angelis et al [18], who used fractional 1540-nm Er:glass. Following treatment, they found an increase in collagen fibers by hydroxyproline assay and H&E, respectively, and they concluded that histological changes could have preceded the significant clinical improvement.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The histological findings in the present study are in agreement with those of Jiménez et al [15], who used PDL, and in agreement with De Angelis et al [18], who used fractional 1540-nm Er:glass. Following treatment, they found an increase in collagen fibers by hydroxyproline assay and H&E, respectively, and they concluded that histological changes could have preceded the significant clinical improvement.…”
Section: Discussionsupporting
confidence: 93%
“…Few side effects were reported by Goldman et al [12], who used the long-pulsed 1064-nm Nd:YAG (transient edema and erythema), and by De Angelis et al [18], who used They concluded that their laser were safe for use. However, Jiménez et al [15] and Tay et al [19] did not recommend the use of their lasers (PDL and diode laser, respectively) in patients with dark skin because of the potential side effect of postinflammatory hyperpigmentation, which occurred at a high frequency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various laser systems are currently being promoted for their treatment. [2,7,8] The non-ablative long pulse Nd: YAG laser and ablative Er: YAG laser have been suggested as effective methods of treatment for striae distensae in previous studies. When we compared the efficacy of these two methods, patients with the mature, alba type of striae distensae had poor clinical improvement with both laser types.…”
Section: Discussionmentioning
confidence: 99%